Polyploidization and Cancer - Poon, Randy Y. C.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Limiting genome replication to once per cell cycle is vital for maintaining genome stability. Although polyploidization is of physiologically importance for several specialized cell types, inappropriate polyploidization is believed to promote aneuploidy and transformation. A growing body of evidence indicates that the surveillance mechanisms that prevent polyploidization are frequently perturbed in cancers. Progress in the past several years has unraveled some of the underlying principles that maintain genome stability. This book brings together leaders of the field to overview subjects relating to polyploidization and cancer.
Polyploidy, Aneuploidy and the Evolution of Cancer -- Molecular Mechanisms and Function of the Spindle Checkpoint, a Guardian of the Chromosome Stability -- Understanding Cytokinesis Failure -- DNA Damage and Polyploidization -- Role of the p53 Family in Stabilizing the Genome and Preventing Polyploidization -- Centrosomes, Polyploidy and Cancer -- Polyploidy: Mechanisms and Cancer Promotion in Hematopoietic and Other Cells -- Polyploidization of liver cells -- Analysis of Cellular DNA Content by Flow and Laser Scanning Cytometry.
Keywords: Medicine; Biomedicine; Biomedicine general; Electronic books